A Comparative Study of Three Different Techniques of Placing Calcium Hydroxide as Intra-Canal Dressing - Behnam, Ihsan N. (Zanco Journal of Medical Sciences (ZJMS), 2009)
Background and objective: Calcium hydroxide used in modern root canal therapy as intra-canal dressing. It is used due to its antimicrobial effect. In this study trhree different techniques of placing calcium hydroxide as intra-canal dressing are used to determine the most effective method of using calcium hydroxide as intra-canal dressing. Methods: Eighteen mandibular premolars were randomly collected, root prepared and filled with calcium hydroxide paste in one of three techniques (1) using file and absorbent paper point with vertical compaction (2) using special syringe with vertical compaction (3) using lentulo drill with vertical compaction. Radiographs were taken to evaluate paste compactness. Results: The placement of calcium hydroxide with lentulo drill aided by vertical compaction showed the lowest number of empty spaces followed by using special syringe with vertical compaction and the highest number of empty spaces was shown by using file aided by absorbent paper point and vertical compaction. Conclusion: The use of lentulo drill aided by vertical compaction gave the best result of using calcium hydroxide paste as intra-canal dressing.